2010
DOI: 10.1128/jvi.02563-09
|View full text |Cite
|
Sign up to set email alerts
|

Route of Adenovirus-Based HIV-1 Vaccine Delivery Impacts the Phenotype and Trafficking of Vaccine-Elicited CD8 + T Lymphocytes

Abstract: Candidate HIV-1 vaccine regimens utilizing intramuscularly (i.m.) administered recombinant adenovirus (rAd)-based vectors can induce potent mucosal cellular immunity. However, the degree to which mucosal rAd vaccine routing might alter the quality and anatomic distribution of vaccine-elicited CD8 ؉ T lymphocytes remains unclear. We show that the route of vaccination critically impacts not only the magnitude but also the phenotype and trafficking of antigen-specific CD8 ؉ T lymphocytes in mice. I.m. rAd immuniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 46 publications
3
66
0
Order By: Relevance
“…with 10 7 virus particles (vp) of rAd5.SIVgag (rLm alone, n ϭ 4/group; rLm-rAd5, n ϭ 4/group). Animals were bled weekly, and vaccine-elicited CD8 ϩ T lymphocyte responses specific for the dominant SIV Gag AL11 epitope (AAVKNWMTQTL, H2-D b ) (6) were monitored by tetramer binding assays (7,8). As shown in Fig.…”
mentioning
confidence: 99%
“…with 10 7 virus particles (vp) of rAd5.SIVgag (rLm alone, n ϭ 4/group; rLm-rAd5, n ϭ 4/group). Animals were bled weekly, and vaccine-elicited CD8 ϩ T lymphocyte responses specific for the dominant SIV Gag AL11 epitope (AAVKNWMTQTL, H2-D b ) (6) were monitored by tetramer binding assays (7,8). As shown in Fig.…”
mentioning
confidence: 99%
“…Among them, the adenoviral-based TB vaccines have gained increased attention, as they were first evaluated as mucosal TB vaccine candidates (15). An increasing number of studies have thus focused on mucosal immunity; these studies have suggested that intranasal/intrapulmonary vaccination with recombinant adenoviral vaccines may induce an antigen-specific mucosal immune response (15,(61)(62)(63)(64)(65)(66). In line with these findings, the results of the present study demonstrated that intranasal boost with the recombinant adenovirus Ad5-CEAB was able to enhance the BCG-primed immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In connection with this, vaccines providing protection against gastrointestinal infectious diseases must be able to induce long-term mucosal immune responses [3][4][5][6][7][8][9]. Previously, we demonstrated that long-lasting protection against mucosal viral transmission could be accomplished by CD8 1 CTLs that must be present at the mucosal site of antigen exposure, although some mucosal memory CTLs may be induced even after systemic vaccination [10][11][12][13][14][15][16]. This protective effect was ablated when CD8 1 cells were depleted in vivo, and required that CTLs were present in the gut mucosa, whereas splenic CTLs alone were unable to protect against mucosal viral challenge [10].…”
Section: Introductionmentioning
confidence: 99%